2016
DOI: 10.1002/2015rg000515
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating hydrological processes at the soil‐vegetation‐atmosphere interface with water stable isotopes

Abstract: Water stable isotopes (18O and 2H) are widely used as ideal tracers to track water through the soil and to separate evaporation from transpiration. Due to the technical developments in the last two decades, soil water stable isotope data have become easier to collect. Thus, the application of isotope methods in soils is growing rapidly. Studies that make use of soil water stable isotopes often have a multidisciplinary character since an interplay of processes that take place in the vadose zone has to be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
382
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 423 publications
(442 citation statements)
references
References 277 publications
29
382
5
1
Order By: Relevance
“…This "two-water-world" hypothesis (McDonnell, 2014) is controversial (Berry et al, 2017;Sprenger et al, 2016) and could be at odds with the existence of subsurface reservoirs such as layers of saprolite and fractured, partly weathered immobile material that hold water that is accessed by trees (Oshun et al, 2016). For example, in seasonally dry climates, trees may derive a significant portion of their moisture from immobile weathered material well below the soil (Zwieniecki and Newton, 1996;Graham et al, 2010;Nie et al, 2012).…”
Section: Hypothesis 6 Trees Grow the Majority Of Their Rootsmentioning
confidence: 99%
“…This "two-water-world" hypothesis (McDonnell, 2014) is controversial (Berry et al, 2017;Sprenger et al, 2016) and could be at odds with the existence of subsurface reservoirs such as layers of saprolite and fractured, partly weathered immobile material that hold water that is accessed by trees (Oshun et al, 2016). For example, in seasonally dry climates, trees may derive a significant portion of their moisture from immobile weathered material well below the soil (Zwieniecki and Newton, 1996;Graham et al, 2010;Nie et al, 2012).…”
Section: Hypothesis 6 Trees Grow the Majority Of Their Rootsmentioning
confidence: 99%
“…The frequently measured soil water isotope data we have presented and the inherent evaporation signal can help to calibrate or benchmark the representation of soil-vegetationatmosphere interactions in tracer-aided hydrological modeling from the plot (Rothfuss et al, 2012;Sprenger et al, 2016b) to the catchment scale van Huijgevoort et al, 2016). So far, the isotopic composition of mobile water has been used to better constrain semi-distributed models van Huijgevoort et al, 2016).…”
Section: Vegetation Affects Critical Zone Evaporation Lossesmentioning
confidence: 99%
“…Such enrichment from kinetic fractionation was found in soil water isotopes across various climatic regions, with more pronounced evaporative signals reaching deeper into the soils in arid and Mediterranean environments than in temperate regions (Sprenger et al, 2016b). However, the temporal variability of the isotopic fractionation in the field has not yet been studied, despite recent technical developments that enabled easier analysis of stable isotopes in soil water (see review by Sprenger et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…McCutcheon, McNamara, Kohn, and Evans (2017) suggested that cannot relate soil water mobility to isotopic composition, and the isotopic distinction between root-absorbed and draining waters may not be an appropriate indicator of ecohydrological separation of soil waters. Sprenger, Leistert, Gimbel, and Weiler (2016) proposed that subsequent mixing of the evaporated soil water with nonfractionated precipitation water (i.e., subsequent fading of fraction effects) could explain the differences in the isotopic signal of water in the top soil and in the xylem of plants on the one hand and groundwater and streamwater on the other hand. Sprenger, Leistert, Gimbel, and Weiler (2016) proposed that subsequent mixing of the evaporated soil water with nonfractionated precipitation water (i.e., subsequent fading of fraction effects) could explain the differences in the isotopic signal of water in the top soil and in the xylem of plants on the one hand and groundwater and streamwater on the other hand.…”
mentioning
confidence: 99%